Audio Described vs. Audiovisual Porn: Cortisol, Heart Rate and Engagement in Visually Impaired vs. Sighted Participants - Rojo López, Ana M; Ramos Caro, Marina; Espín López, Laura (Frontiers in Psychology, 2021)
Audio description remains the cornerstone of accessibility for visually impaired audiences to all sorts of audiovisual content, including porn. Existing work points to the efficacy of audio description to guarantee immersion and emotional engagement, but evidence on its role in sexual arousal and engagement in porn is still scant. The present study takes on this challenge by comparing sighted and visually impaired participants’ experiences with porn in terms of their physiological measures of arousal—i.e., cortisol and heart rate—and self-reported measures of affect, anxiety, sexual reactivity, and narrative engagement. 69 Spanish participants were allocated into three different groups: participants who watched and heard the porn scenes in their audio-visual version (AV); participants who listened to the audio described version without images (AD); and visually impaired participants who also listened to the audio described version without images (ONCE). The analysis of cortisol reactivity to porn revealed no significant differences between the groups, but pointed to a higher percentage of non-responders in the three groups, the highest being found in the ONCE group. As for participants’ cardiac response to the clips, no significant differences were found across the groups, with the highest heart rate levels being registered in the baseline phase. Self-report measures revealed significant between-group differences in negative affect. The ONCE group revealed the highest pre-task levels of negative affect and was the only group that showed a decrease in negative affect after exposure to the clips. Sighted and visually impaired participants reported to be moderately aroused and immersed in the films, regardless of exposure to AV or AD porn. In addition, correlations reported between participants’ levels of self-report sexual arousal and transportation and post-task affect pointed to a positive relationship between exposure to porn and perceived levels of sexual arousal and affect. Results from the study point to the efficacy of audio description in providing sighted and visually impaired audiences with a similar experience to that offered by original AV porn scenes. This study is exploratory but provides valid, initial groundwork for further research on the impact of audio description on porn reception.